Indian Neurotherapy in Obsessive–Compulsive Disorder (OCD) Management - A Case Report (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
by persistent intrusive thoughts and compulsive behaviours causing severe functional impairment. Despite pharmacological and psychotherapeutic advances, a substantial proportion of patients experience incomplete response, relapse, or limited access to evidence-based care. Indian Neurotherapy, a non-invasive naturopathic system employing targeted neuromuscular stimulation, offers a potentially viable complementary approach, yet remains undocumented in peer-reviewed clinical literature. Objective: To evaluate clinical outcomes of structured Indian Neurotherapy in a severe, treatment-refractory OCD case using the OCI-R as primary outcome measure, with 10-month follow-up. Methods: CARE-compliant observational single-case study at LMNTRTI, Punjab, India. Participant: 43-year-old female with 25-year OCD history, multiple comorbidities, and prior treatment failure across allopathic, Ayurvedic, and homoeopathic systems. OCI-R administered at baseline (14 June 2025), after 6 sessions (20 June 2025), post-intervention (22 August 2025), and followed up to 11 March 2026 (9 months). Results: OCI-R scores: 69/72 (severe) → 35/72 (49.3% reduction after 6 sessions) → 0/72 (complete remission at 10 weeks). At 9-month follow-up, the participant returned for general wellness goals with no OCD symptom recurrence. Conclusion: This CARE-compliant case report demonstrates complete, sustained remission of severe, long-standing OCD through Indian Neurotherapy, with mechanistic plausibility grounded in autonomic, vagal, serotonergic, and neurochemical regulatory pathways. Controlled trials are urgently warranted.